Comparative study between shell eggs and egg rolls stored under ambient and refrigerated conditions - Pato, Norinna G.; Alabastro, Estrella F. (1981.)
ABSTRACT The behavior of hard-cooked shell eggs and egg roll under ambient and refrigeration conditions were studied in this research. To limit variations in raw materials, only raw shell eggs which floated in 12° sal were used, as was determined during the preliminary phase, since at this flotation concentration, raw eggs have a pH of around 7.1. During storage under ambient conditions, discolorations as well as softening or wetting of the yolk and albumen; and strengthening of off-odor were observed in egg rolls, and to a lesser extent, in egg rolls generally started earlier than in shell eggs, though the exact time was difficult to pinpoint base on sensory evaluation. The pH readings of both products increased during the first few days them gradually decreased until both products were slightly acidic. Microbiological evaluation showed that the cooking process was enough to control the coliforms and Salmonella species. Total plate counts reached the critical point of 25,000 microorganisms per gram between the 4th and 6th days for egg rolls and between the 6th and 7th days for shell eggs. Under refrigeration conditions, trends in pH readings were similar to those in the first phase, though the changes were much slower. Changes in color and texture were too slight to be considered as indicators of spoilage, development of oo-odor, though was quite fast for both. In fact, starting on the 6th day of the 14 day storage, the characteristics egg odor was nearly gone in both products. Microbiological evaluation pinpointed the 5th day to be the critical time for egg roll while for shell eggs, it occurred between the 6th and 7th days.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Eggs -- Storage